Study of the Chemical and Pb Isotope Composition in Dirhams from the Podbolotyevo Cemetery - Irina A. Saprykina; Andrey V. Chugaev; Olga V. Zelentsova; Bulat A. Bakirov; Sergey E. Kichanov (Нижневолжский археологический вестник, 2023)
A series of silver dirhams and their imitations, originating from the burials of the Podbolotyevo burial ground left by the Muroma tribe, was studied by XRF, neutron diffraction and analysis of the isotopic composition using the Pb-Pb method. The burial ground is located near the city of Murom, Vladimir Region of Russia. The collection obtained from the excavations of this site includes finds of 40 original Arabic silver coins and silver coin replicas. The analyzed sample consists of 34 coins and includes dirhams dating back to the 9th century BC which are replicas of the Abassid dirhams; and the main array of coins dates back to the first third of the 10th century and the second half of the 10th century. The chemical composition studies of the metal by X-ray diffraction method showed that high-grade, “yellow” and multicomponent silver were used for minting dirhams. It was found out that there is a sharp drop in the silver content in the dirhams dating back from the middle to the second half of the 10th century, which reflects the general trend in Arabic coinage. It is also noted that in the sample from the Podbolotyevo burial ground, dirhems coin replica coins were made of high-grade silver. Silver purity for some of the coins from the analyzed sample was checked by neutron diffraction using a specialized DN-6 diffractometer at the IBR-2 high-flux reactor. The isotopic composition of lead in silver in coins from the analyzed sample was studied by the method of multicollector mass spectrometry with ionization of matter in inductively coupled plasma (MC-ICP-MS). The obtained data on the isotopic composition of Pb in the silver of the coins showed that the precious metal for minting both Arab dirhams at the mints of ash-Shash, Samarkand, Bukhara, and their replicas comes from the deposits in Central Asia. It has been established that the Lashkerek and Ilak deposits turned out to be the source of silver for some dirhams from the Podbolotyevo burial ground, however, mixed silver from several deposits was mainly used.